Microbiome-metabolome analysis insight into the effects of high-salt diet on hemorheological functions in SD rats - Qi, Luming; Li, Yao; Chen, Zhixuan; Wei, Changhong; Wen, Xue; Hu, Shuangyan; Wu, Hang; Lv, Zhuoheng; Xu, Zhangmeng; Xia, Lina (Frontiers in Nutrition, 2024)
The present study examined the effect of two dietary regimens with elevated salt concentrations (4% and 8% salt) on hemorheological functions of SD rats, and explored the underlying mechanisms mainly through microbiome-metabolome analysis. An 8% HSD substantially altered the hemorheological parameters, and compromised intestinal barrier integrity and reduced the short-chain fatty acid levels. The microbiome-metabolome analysis revealed that 49 genusspecific microorganisms and 156 metabolites showed a consistent trend after exposure to both 4% and 8% HSDs. Pathway analysis identified significant alterations in key metabolites within bile acid and arachidonic acid metabolism pathways. A two-sample Mendelian randomization (MR) analysis verified the link between high dietary salt intake and hemorheology. It also suggested that some key microbes and metabolites (such as Ruminococcaceae UCG-005, Lachnospiraceae NK4A136, Ruminiclostridium 6, and Ruminococcaceae UCG-010, TXB-2, 11,12-diHETrE, glycochenodeoxycholate) may involve in abnormalities in blood rheology caused by high salt intake. Collectively, our findings underscored the adverse effects of high dietary salt on hemorheological functions and provide new insight into the underlying mechanism based on microbiome-metabolome analysis.